Human recognition using wireless router signal - Chowdhury, S. M. A. Muksit; Shawon, Hasinur Are n; Patwary, Tanvir Wazy Ullah; Rahman, Rukshanda (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.